The Dynamics of Ethnic Conflict in Southern Province Thailand - Firmansah, Andi (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2019)
This paper explains how the ethnic conflict process that occurred in the Southern Province of Thailand to the process of resolving conflicts between the Government of Thailand and local residents in the Southern Province of Thailand. The conflict is based on the history of the Southern Thailand region between the Thai Government and the Malay Muslim population. Then, it caused conflicting attitudes and behaviors in responding to this conflict from each of the warring parties. This paper uses the concept of the conflict triangle from Johan Galtung where this conflict comes from perceptions based on historical differences, then followed by differences in conflicting behavior from each party and differences in interests. Then, using the concept of the source of conflict from Bernard Meyer, the source of the conflict that comes from historical differences so that it affects how to communicate, emotional reactions, values ??and structures owned. Then, using the concept of the stage of conflict resolution from Johan Galtung, this conflict is at the peacekeeping level where Malaysia is the mediator between the two warring parties. In resolving conflicts, both parties need to change attitudes and behavior in transforming different interests.